Crystal structure of the fungal nitroreductase Frm2 from Saccharomyces cerevisiae - Song, Hyung-Nam (Protein Sci, 2015)
Nitroreductases are flavoenzymes that catalyze nitrocompounds and are widely utilized in industrial applications due to their detoxification potential and activation of biomedicinal prodrugs. Type I nitroreductases are classified into subgroups depending on the use of NADPH or NADH as the electron donor. Here, we report the crystal structure of the fungal nitroreductase Frm2 from Saccharomyces cerevisiae, one of the uncharacterized subgroups of proteins, to reveal its minimal architecture previously observed in bacterial nitroreductases such as CinD and YdjA. The structure lacks protruding helical motifs that form part of the cofactor and substrate binding site, resulting in an open and wide active site geometry. Arg82 is uniquely conserved in proximity to the substrate binding site in Frm2 homologues and plays a crucial role in the activity of the active site. Frm2 primarily utilizes NADH to reduce 4-NQO. Because missing helical elements are involved in the direct binding to the NAD(P)H in group A or group B in Type I family, Frm2 and its homologues may represent a distinctive subgroup with an altered binding mode for the reducing compound. This result provides a structural basis for the rational design of novel prodrugs with the ability to reduce nitrogen-containing hazardous molecules. PDB Code(s): 4urp